Forensic Aspects Of Dental Fractures (Eurasian Medical Research Periodical, 2024)
The article notes that tooth fractures can occur in the crown and neck regions, as well as in the root region. In this case, the strength properties of teeth increase depending on the order of their arrangement, as a result, fractures of large masticatory teeth are relatively rare and occur predominantly in fractures of the jaw or its alveolar process. They can also be transverse, oblique, and vertical with respect to the axis of the tooth. The tooth cervix refers to the weakest part of the crown in terms of strength, and fractures occurring here are usually complete